Acceptance and Commitment Therapy pada Pasien Skizofrenia dengan Halusinasi - Yoduke, Fandy; Daulima, Novy Helena Catharina; Mustikasari, Mustikasari (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of acceptance and commitment therapy in schizophrenic patients with hallucinations. The method used in this study is a systematic literature review with a structured and systematic search on Embase, Clinical Nurse Key, and Scopus databases using the keywords acceptance and commitment therapy AND hallucinations OR hallucinations. The search results on the database contained in him 5 related articles that are eligible to be synthesized and correspond to the theme stating that acceptance and commitment therapy in schizophrenic patients with hallucinations is an effective therapy and can be used as group therapy in community care. Conclusion The use of acceptance and commitment therapy can be applied in providing interventions to hospital, group, and community care patients. Keywords: ACT, Acceptance and Commitment Therapy, Hallucinations